Regenerasi Minyak Jelantah Dengan Proses Adsorpsi Menggunakan Ampas Nanas (Ananas comosus) - Suraiya Kamaruzzaman; Mariana Mariana; Ryka Mutiara Sari; Mutia Ulfa (Jurnal Inovasi Ramah Lingkungan, 2020)
Used cooking oil is cooking oil that has been used a few times of use. Besides the color unattractive and rancid, used cooking oils also have enormous potential to harm health. This study aims to clarify the re-use cooking oil with pineapple pulp as an adsorbent so that the oil can be reused properly. Pineapple (Ananas comosus) rich in the enzyme bromelein, and vitamin C which act as antioxidants to counteract free radicals the used cooking oil.The results showed that the purification of waste cooking oil use pineapple pulp successfully reduced acid number, saponification and peroxide. The best conditions in this study were at the time of immersion of 72 hours and 15gram mass of adsorbent for the treatment of activated adsorbent. The best value obtained was 0.25%; 199,155 and 1.6 mEq that has been qualified in accordance with SNI quality cooking oil..